Appraisal Language in Examples of Promotional Discourse - Al-Attar, Maryam Mahmood Hikmet (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
This study focuses on investigating appraisals in the promotional discourse types of print adverts, Facebook posts, Facebook comments, and customer reviews for cosmetics and cars which were collected from mainstream media, i.e., magazines, and online media, i.e., Facebook pages, and review websites. Although widely known, up until now, no work has studied and compared the employment of appraisals in such discourses. For this purpose, Martin and White’s (2005) theory on appraisal is used as the model to show quantitively and qualitatively the evaluative language employed in these discourses in terms of the attitudinal resources, their polarity and graduation. This study shows that inscribed rather than evoked appraisals feature in all these discourses and that appreciation and affect are the mostly used attitudinal resources in them. It is also found that, unlike the comments and reviews that tend to contain both positive and negative appraisals, the adverts and posts are entirely positive in their appraisals. Finally, although these discourses are found to be evaluative, ungraduated evaluations characterise the adverts, posts, and comments compared to the more graduated appraisals in reviews.